2020
DOI: 10.1038/s41467-019-14178-y
|View full text |Cite
|
Sign up to set email alerts
|

β4GALT1 controls β1 integrin function to govern thrombopoiesis and hematopoietic stem cell homeostasis

Abstract: Glycosylation is critical to megakaryocyte (MK) and thrombopoiesis in the context of gene mutations that affect sialylation and galactosylation. Here, we identify the conserved B4galt1 gene as a critical regulator of thrombopoiesis in MKs. β4GalT1 deficiency increases the number of fully differentiated MKs. However, the resulting lack of glycosylation enhances β1 integrin signaling leading to dysplastic MKs with severely impaired demarcation system formation and thrombopoiesis. Platelets lacking β4GalT1 adhere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 69 publications
3
27
0
Order By: Relevance
“…Disrupted tight junction signaling in mucosa could possibly explain a response to the breakdown of the integrity of epithelial tight junctions (50). Notably, the current study indicated that MF diet reduced the expression of genes involved in key pathways (epithelial adherens junction, integrin, and ILK signaling) that regulate tight junctions in IL (51,52). Several pathogens invade hosts by taking advantage of the dysregulation of tight junctions in mucosal cells (53).…”
Section: Discussionmentioning
confidence: 64%
“…Disrupted tight junction signaling in mucosa could possibly explain a response to the breakdown of the integrity of epithelial tight junctions (50). Notably, the current study indicated that MF diet reduced the expression of genes involved in key pathways (epithelial adherens junction, integrin, and ILK signaling) that regulate tight junctions in IL (51,52). Several pathogens invade hosts by taking advantage of the dysregulation of tight junctions in mucosal cells (53).…”
Section: Discussionmentioning
confidence: 64%
“…We observed variability of the RCA/FSC ratio in our population. We found various single nucleotide polymorphisms (database AWESOME) 45 in 3 genes involved in platelet glycosylation/sialylation: SLC35A1 , GNE and B4GALT1 46 . This analysis demonstrated that the variability observed could be explained by a genetic variation.…”
Section: Discussionmentioning
confidence: 70%
“…While alterations in the activity of some of the β4GalT subfamily members have been associated with various diseases, 8,9 our recent data shows that deletion of the B4GALT1 leads to severe thrombocytopenia and impaired HSC homeostasis. 10 Additionally, in megakaryocytes B4GALT1 expression is regulated via the JAK signaling to control glycan expression on proteins. 10,11 Thus, galactosylation regulated by JAK plays an important role in megakaryopoiesis.…”
Section: Introductionmentioning
confidence: 99%